2017
DOI: 10.22256/pubvet.v11n5.470-475
|View full text |Cite
|
Sign up to set email alerts
|

Brucella ovis and Brucella abortus in sheep herds of Teresina, Brasil

Abstract: The purpose of this study was to conduct an epidemiological investigation on the occurrence of Brucella ovis and Brucella abortus in sheep flocks at municipalities belonging to the microregion of Teresina, Piauí, Brazil. Samples from 521 animals were analyzed. It was performed blood collection by venous access, and the tubes containing the samples were sent to the Laboratory of Pathophysiology of Reproduction of Domestic Animals of the Federal University of Piauí, for later analysis. It was performed the antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In Brazil, there are few studies on Brucella abortus, specifically in sheep, due to the predictive behavior of this microorganism. Several studies conducted in Brazil corroborate with our results, wherein all evaluated animals were seronegative (Nozaki et al, 2004;Salabarry et al, 2011;Silva et al, 2017). However, other studies have reported the occurrence of anti-B.…”
Section: Resultssupporting
confidence: 91%
“…In Brazil, there are few studies on Brucella abortus, specifically in sheep, due to the predictive behavior of this microorganism. Several studies conducted in Brazil corroborate with our results, wherein all evaluated animals were seronegative (Nozaki et al, 2004;Salabarry et al, 2011;Silva et al, 2017). However, other studies have reported the occurrence of anti-B.…”
Section: Resultssupporting
confidence: 91%